OYÍN ATQARÍWSHÍLARDÍŃ SAXNADA JAYLASÍWÍ – XOREOGRAFIYALÍQ SÍZÍLMA (ART AND CULTURE BULLETIN, 2026)
This article provides information on the placement of performers on stage, playing patterns, artist images, and choreographic drawings. The choreographer provided information on the variety of dance patterns or pictures.
Keywords: ballet master, choreography, composition, performance, stage, improvisation, performance, artistic image